Analisis Kompetensi Siswa Sekolah Dasar dalam Menulis dan Memahami Struktur Pantun Dikota Padang - Warisa Hadi Amelsi; Chandra Chandra; Inggria Kharisma (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
One of the problems raised in this study is the low ability of elementary school students to write and understand the structure of rhymes, especially in Padang City. The purpose of this study is to describe the ability of Phase B students (grade IV of elementary school) to write rhymes from a cognitive and psychomotor perspective. The cognitive aspect assesses students' understanding of the structure and function of the rhyme, while the psychomotor aspect assesses the student's ability to compose rhymes in accordance with rules such as rhyme, the number of lines, and the relationship between rhyme and content. Warisa Hadi Amelsi conducted this research with a descriptive qualitative approach with a case study of five students in the fourth grade in one of the elementary schools in Padang City. The results of the study showed that the Indonesian Phase B learning achievement indicators were used to make assessment instruments. The results show that students' abilities are still low, with a high score of 70 and an overall average of 49. While most students know the characteristics of rhymes, they face difficulties in writing complete and organized rhymes. The results suggest that more contextual and creative learning strategies should be strengthened. In addition, students must be trained to write and understand ancient types of literature such as rhymes. It is hoped that this research will be a reference for the development of evaluation of Indonesian learning in elementary schools.